Multidisciplinary Approach in the Treatment of a Rare Surgical Disease Trichobezoar in an 11-year-old Child: Clinical Case - Elena Yu. Dyakonova; Maksim M. Lokhmatov; Mikhail V. Ryazanov; Aleksandr S. Bekin; Aleksey A. Gusev; Svetlana B. Lazurenko; Anna S. Buslaeva (Union of pediatricians of Russia, 2017)
Bezoars are rarely occurring foreign bodies of the gastrointestinal tract, only 0.5-1% of cases cause the mechanical intestinal obstructions. It is very difficult to diagnose bezoar on early stages. The presented clinical case demonstrates the opportunities of multidisciplinary approach in diagnosis and rehabilitation of children with trichobezoar. Two weeks before hospitalization, the girl began to make complaints about periodic abdominal pain, nausea, episodes of vomiting occurred immediately after ingestion. The child underwent complex examination (including esophagogastroduodenoscopy) which revealed a giant trichobezoar occupying the entire lumen of the stomach. Gastrotomy, removal from the stomach in the form of his «impression» trichobezoar (12×15 cm) was performed. During the in-patient monitoring at hospital, both medical assistance and psychological and pedagogical support was provided to the child and to his parents as well; consultations on emotional state of the child and optimizing the process of education in the family were delivered. The joint work of pediatricians, surgeons, and specialists in the psychological and pedagogical service makes it possible to determine the necessary volume of medical assistance, as well as the psychological reason for the occurrence of neurotic reactions to prevent the «hair tumor» formation in future.